ECONOMIC STRUCTURE, ENERGY TRANSITION, AND CARBON EMISSIONS IN ASEAN MARITIME STATES : PANEL ARDL APPROACH - Indah Susilowati; Muhammad Fahrur Rozi; Ismiyati; Dwijaya Samudra Suryaman; Maratus Sholikhah (RADJA PUBLIKA, 2026)
This study analyzes the factors influencing carbon emissions in five ASEAN maritime countries, namely Indonesia, Philippines, Thailand, Malaysia, and Vietnam, using the Panel Autoregressive Distributed Lag (P-ARDL) method with data from 1993 to 2023. The variables studied include economic growth, energy intensity, the share of renewable energy, and sector structure using the agriculture industry proxy. Long-term estimates show that GDP per capita growth, energy intensity, and sector structure have a significant positive effect on carbon emissions, while renewable energy has a negative but insignificant effect. In the short term, energy intensity is the most dominant factor increasing emissions, while economic growth, renewable energy, and sector structure have not shown a significant impact. Vietnam and Thailand are still in the early phase of the Environmental Kuznets Curve (EKC), while the Philippines and Malaysia are beginning to show decoupling through energy efficiency and the service sector. Indonesia shows an unstable transition pattern. These findings emphasize the need to improve energy efficiency and accelerate the clean energy transition in ASEAN maritime countries.